Poor outcomes after hepatectomy in patients with ascites infected by methicillin‐resistant staphylococci. (22nd October 2014) - Nitta, Hidetoshi; Beppu, Toru; Itoyama, Akari; Higashi, Takaaki; Sakamoto, Keita; Nakagawa, Shigeki; Mima, Kosuke; Okabe, Hirohisa; Imai, Katsunori; Hayashi, Hiromitsu; Hashimoto, Daisuke; Chikamoto, Akira; et al.
Abstract Background This study was designed to investigate the association between infectious ascites, clinical parameters and treatment outcomes after hepatectomy. Methods Of 891 patients who underwent hepatectomy between 2006 and 2013, 74 who underwent paracentesis for bacterial cultivation of postoperative ascites after hepatectomy were analyzed. Results Of the 74 patients, 42 had positive bacterial cultures (positive group) and 32 patients had negative cultures (negative group). Hospital mortality was significantly higher in the positive group than in the negative group [9/42 (21.4%) vs. 2/32 (6.3%); P = 0.035]. Hospital mortality associated with each bacterial strain was as follows: methicillin‐resistant staphylococci (MRS) (5/13, 38.5%), staphylococci (2/11, 18.2%), enterococci (2/12, 16.7%), Enterobacter (0/3, 0%), Klebsiella (0/2, 0%), and others (0/1, 0%). Cox proportional multivariate analysis revealed that MRS infection in ascites was the only risk factor of hospital death (HR = 5.08, P = 0.041) and MRS wound infection was the only risk factor to predict MRS infection in ascites (HR = 5.67, P = 0.015). Conclusion Postoperative MRS infection in postoperative ascites after hepatectomy is a potentially fatal complication; therefore, the prevention of MRS wound infection is critical to decrease postoperative hospital mortality.